A virtual sub‐internship for otolaryngology‐head and neck surgery. Issue 5 (18th August 2021) - Bernstein, Jeffrey D.; Ball, Laurel L.; Nardone, Zachary B.; Watson, Deborah
Abstract: Objective: During the COVID‐19 pandemic, away rotations were suspended for safety purposes. This led to the development of online interactive learning modules for students, now known as virtual sub‐internships (VSIs). To date, VSIs within otolaryngology‐head and neck surgery (OHNS) have been limited in their description and design. Study design: Cross‐sectional survey. Setting: ACGME‐accredited OHNS residency program. Methods: Our curriculum for an OHNS VSI is presented. Based on the model used by our OHNS residency program, the VSI consisted of a 2‐week block of activities and interactive small‐group discussions. A post‐VSI feedback survey was distributed to participants; results are reported. Results: Six 2‐week VSI sessions were administered. Twenty‐one individuals participated from all US regions, median 4 individuals per session. Fifteen participants (71.4%) completed the feedback survey. Of survey respondents, 20% lacked a home OHNS residency program, and no respondents' home‐programs featured a VSI. All respondents were satisfied with the schedule and organization of the VSI, and 73.3% (11 of 15) felt it was of appropriate duration. All respondents reported a high degree of familiarity with the program, with a greater (86.7%) or equal (13.3%) level of interest in applying to the residency program as a result of participating in the VSI. Conclusion: This VSI curriculum offers a well‐received virtual learning experience for medical students applying to OHNS residency. It provides an opportunity for programs to expand their appeal to potential applicants who may otherwise be restricted in their ability to travel. Abstract :